Can People Be Managed through Fear? An Enquiry into Arab Culture - Abdulrahman Essa Al Lily; Ahmed Ali Alhazmi (Behavioral Sciences, 2022)
This research scrutinises the fear-driven management of Arabs. It conceptualises fear as a structural component of Arab society through a sociological lens and, by drawing upon the reflections of 28 Arab experts, philosophises on the potential of fear to develop into a well-configured managerial system (‘feararchy’) that regulates public and private lives. This research finds this system to rest upon a foundation of three forms of fear: ontological (the normalisation of fear), epistemological (the utilisation of fear to shape knowledge) and axiological (the influence of fear on acceptability). This article makes five contributions. First, it shows how, through turning fear into a collective status, Arab managers exploit fear for social control. Second, it demonstrates the institutional nature of Arabs’ fear, making it worthy of attention from the field of management. Third, it investigates fear as an individually internalised, socially constructed feeling that is psychologically manipulative. Fourth, it presents fear as not merely a natural psychological sensation but a managerially distorted contextual frame within which current (and future) members think and operate. Fifth and finally, it exposes the contextuality of fear: sources of fear in one context may not be sources of fear in another.